EXPLORING CO - CREATION IN SMALL MEDIUM ENTERPRISES (SMes): STRATEGY, IMPLEMENTATION AND CHALLENGES - Handayani, Made; Sri Darma, Gede; Oka Martini, Ida Ayu (Jurnal Riset Bisnis dan Manajemen, 2025)
This study aims to explore co-creation applied by small and medium enterprises. Various studies on co-creation have been conducted,but there are still few that specifically explain the implementation strategy and challenges of SMEs in implementing co-creation, most suggest the application of innovation in the implementation of SME strategy. This review uses 53 literatures over the past 10 years from 2015 to 2024. This review found that the co-creation strategies used by SMEs are customer segmentation, use of digital platforms, building customer communities. The implementation of co-creation in SMEs is in the form of platform-based collaboration, collaboration with suppliers and partners, and providing a fast feedback mechanism. The challenges faced by SMEs in implementing co-creation are limited resources, customer expectation management, lack of expertise in digital technology, and intellectual property risks.